2021
DOI: 10.1016/j.bandl.2021.104960
|View full text |Cite
|
Sign up to set email alerts
|

The organization of the American Sign Language lexicon: Comparing one- and two-parameter ERP phonological priming effects across tasks

Abstract: We used phonological priming and ERPs to investigate the organization of the lexicon in American Sign Language. Across go/no-go repetition detection and semantic categorization tasks, targets in related pairs that shared handshape and location elicited smaller N400s than targets in unrelated pairs, indicative of facilitated processing. Handshape-related targets also elicited smaller N400s than unrelated targets, but only in the repetition task. The location priming effect reversed direction across tasks, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
(62 reference statements)
1
11
0
Order By: Relevance
“…Gutiérrez et al (2012) hypothesized that the increased N400 negativity for signs sharing location reflects lexical competition via lateral inhibition. Meade et al (2021a) reported similar results for ASL and provided further support for this hypothesis. Deaf ASL signers performed either a go/no-go repetition detection task which could be performed based only on perceptual processing (lexical access/selection is not required) and a go/ no-go semantic categorization task (is this a country sign?)…”
Section: Perception Of Sublexical Phonological Structuresupporting
confidence: 72%
See 2 more Smart Citations
“…Gutiérrez et al (2012) hypothesized that the increased N400 negativity for signs sharing location reflects lexical competition via lateral inhibition. Meade et al (2021a) reported similar results for ASL and provided further support for this hypothesis. Deaf ASL signers performed either a go/no-go repetition detection task which could be performed based only on perceptual processing (lexical access/selection is not required) and a go/ no-go semantic categorization task (is this a country sign?)…”
Section: Perception Of Sublexical Phonological Structuresupporting
confidence: 72%
“…Bilateral SMG may be involved in the integration of phonological parameters during sign perception, as only signers exhibited sensitivity in SMG to phonological violations (Cardin et al, 2016). The electrophysiological data indicate that signers develop neural sublexical representations of handshapes and locations that can be primed (Meade et al, 2021a; see also Meade et al, Forthcoming). In addition, lateral inhibition between signs sharing location results in an increased N400 response when lexical selection is required to perform the task (Gutierrez et al, 2012;Meade et al, 2021a).…”
Section: Sign Language Comprehension: Summarymentioning
confidence: 87%
See 1 more Smart Citation
“…The phonological relationship between signs affects processing in ways that bear similarities with findings for spoken words. In recent studies, processing has generally been facilitated when target signs are preceded by prime signs that share two parameters compared to phonologically unrelated prime signs, as reflected in faster responses and smaller amplitude N400s (e.g., Baus, Gutiérrez, & Carreiras, 2014 ; Corina & Knapp, 2006 ; Dye & Shih, 2006 ; Gutiérrez, Müller, Baus, & Carreiras, 2012 ; Meade et al, 2021 ; Meade, Lee, Midgley, Holcomb, & Emmorey, 2018 ). The N400 is a peak in the ERP waveform that occurs approximately 400 ms after word or sign onset and is associated with lexico-semantic processing (see, e.g., Kutas & Federmeier, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…This lack of a rhyming effect in SL suggests that SL users do not associate static locations between signs like rhymes in SpL, despite space representing phonology in SLs. Even when Meade et al 24 found evidence that priming sign location in SL did in fact increase the N400 amplitude, therefore increasing expectancy similarly to SpL, they also found that priming using handshape decreased the N400 amplitude instead. This hierarchical differentiation and inverse effects of priming techniques on sign expectancy are unique to SLs.…”
Section: Comprehension Through Erp Componentsmentioning
confidence: 94%